BIOSURFACTANT PROPERTIES AND ITS APPLICATION IN CHROMIUM REMOVAL: A REVIEW - Usman Ali Bukar; Kawo, Abdullahi Hassan; Yahaya, Sani; Yahaya, Sani; Inuwa, Abdullahi Balarabe; Fardami, Aminu Yusuf (FUDMA JOURNAL OF SCIENCES, 2025)
Chromium contamination primarily originates from anthropogenic activities such as industrial discharges, mining operations, and the improper disposal of chromium-containing products, leading to its infiltration into soil and groundwater. The persistence of chromium in the environment poses severe ecological and health risks, including bioaccumulation in aquatic organisms and adverse effects on plant growth and soil microbes. Human exposure to chromium through contaminated water or occupational settings is linked to respiratory problems, skin disorders, and heightened cancer risk. Addressing these challenges necessitates sustainable remediation approaches, highlighting the potential of biosurfactants as eco-friendly alternatives to conventional methods. This review was aimed to provide an overview on different properties of biosurfactants and its application in chromium removal, covering key aspects from introduction to future perspectives. Biosurfactants as microbial-derived surface-active agents, exhibit properties that make them highly effective in reducing chromium contamination. Their biodegradability, low toxicity, and renewable production ensure minimal environmental impact. Moreover, their amphiphilic nature enhances chromium bioavailability, facilitating microbial uptake and reduction. Certain biosurfactants chelate metal ions, preventing chromium migration and secondary contamination, while their synergistic interactions with microorganisms improve remediation efficiency. By supporting the transformation of toxic Cr (VI) into less harmful Cr (III) and promoting precipitation of insoluble compounds, biosurfactants offer a sustainable and versatile solution for mitigating chromium pollution.